RF-cavity for the X-ray generator NESTOR - Androsov, V.P.; Chernov, K.N.; Gvozd, A.M.; Karnaukhov, I.M.; Ostreyko, G.N.; Sedlyarov, I.K.; Telegin, Y.N. (Вопросы атомной науки и техники, 2007)
In the Kharkov Institute of Physics and Technology 225 MeV electron storage ring NESTOR is under development. The paper describes the design and parameters of a 700 MHz cavity that has been fabricated at BINP for the NESTOR RF-system. Now the low-power and vacuum tests of the cavity are under way at BINP. We present here the results of 3D simulations of the cavity with ANSYS code. The problem of multibunch instabilities in NESTOR is also discussed.